A new genus of Fontinalicaridinae Schminke (Copepoda, Harpacticoida, Parastenocarididae) from Central Brazil, with unique grasping male second pereopod - Corgosinho, Paulo Henrique Costa; Rocha, Carlos Eduardo Falavigna Da; Neves, Gilmar Perbiche; Schizas, Nikolaos V.; Pereira, Ana Clara Ferraz; Castro, Ana Luisa Da Silva (Zootaxa, 2026)
Aggistropodacaris gen. nov., is proposed to accommodate a new species of Fontinalicaridinae found near the National Park of Chapada dos Veadeiros in Goiás, Central Brazil, Tocantins River hydrographic basin. The genus is characterized by a unique morphological adaptation of the males, in which the second pereopod is transformed into a grasping structure. The genus is also characterized by the combination of several characters including 1) a small body size (< 250μm), 2) weak chitinization, 3) lack of integumental windows in the urosome, 4) seven-segmented male antennule, 5) reduced endopod of second pereopod in both male and female, 6) reduced female endopod of third pereopod, 7) elongate endopod of the fourth pereopod reaching midlength of the second exopod in females, and 8) short fifth pereopod in both sexes. Aggistropodacaris gen. nov., is placed within Fontinalicaridinae due to specific apomorphic traits, including the gap between outer setae I-III and dorsal seta VII on the furca, and the bow-like female genital field. Aggistropodacaris gen. nov. shows notable morphological similarities with Siolicaris Jakobi, 1972 and Brasilibathynellocaris Jakobi, 1972, suggesting a close phylogenetic relationship with these genera. The male third pereopod is similar in the new genus and Siolicaris, both with a robust quadratic first exopodite, a short apophysis, and thumb longer than the apophysis with a distal hyaline membrane. The distal hyaline membrane on the male thumb of the third pereopod is also present in Brasilibathynellocaris. Additionally, the fifth pereopod in these three genera is reduced in length, with outer setae located on the distal half. Furthermore, both Aggistropodacaris gen. nov. and Siolicaris exhibit a reduced endopod in the female third pereopod, and the female endopod of the fourth pereopod is longer than the first exopodite, reaching beyond the middle of the second endopodite. This feature is also seen in some species of Brasilibathynellocaris, indicating phylogenetic conservatism across these genera.